2018
DOI: 10.1186/s13046-018-0909-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of cellular reactive oxygen species in cancer chemotherapy

Abstract: Most chemotherapeutics elevate intracellular levels of reactive oxygen species (ROS), and many can alter redox-homeostasis of cancer cells. It is widely accepted that the anticancer effect of these chemotherapeutics is due to the induction of oxidative stress and ROS-mediated cell injury in cancer. However, various new therapeutic approaches targeting intracellular ROS levels have yielded mixed results. Since it is impossible to quantitatively detect dynamic ROS levels in tumors during and after chemotherapy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
458
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 622 publications
(470 citation statements)
references
References 75 publications
7
458
1
4
Order By: Relevance
“…26 Therefore, the quantitative monitoring of dynamic ROS levels in tumours during chemotherapy is vital for effective cancer treatment. 26 In conclusion, our results demonstrated that BNIP3 and ROS are involved in platinum-based combination chemotherapy, while chemo drug-induced autophagy may protect cancer cells from cytotoxicity. Therefore, applying autophagy inhibitors may improve the effects of combination chemotherapy in treating lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Therefore, the quantitative monitoring of dynamic ROS levels in tumours during chemotherapy is vital for effective cancer treatment. 26 In conclusion, our results demonstrated that BNIP3 and ROS are involved in platinum-based combination chemotherapy, while chemo drug-induced autophagy may protect cancer cells from cytotoxicity. Therefore, applying autophagy inhibitors may improve the effects of combination chemotherapy in treating lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…BNIP3 C-terminal phosphorylation in chemo drug-induced cell death still warrants further investigation.The role of ROS in cancer development is paradoxical. Although elevated levels of ROS are involved in cancer progression, higher levels of ROS induced by chemotherapy result in cancer cell death 26. During the oncogenic transformation of tumour cells, persistent metabolic oxidative stress promotes genomic instability and cancer development 25.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, combining ROS-inducing agents with TKI is effective to suppress tumor growth in both STACs xenograft and PDX models, raising the possibility that adjunctive therapies designed to induce ROS accumulation might provide a potential approach to improve EGFR TKI response. Of note, non-selective ROS-inducing agents that globally increase oxidants in cancer have limited therapeutic index due to excessive toxicity in sensitive tissues such as the liver and the nervous system, and many therapeutic approaches targeting intracellular ROS levels have yielded mixed results (Chio and Tuveson, 2017; Yang et al, 2018). Given the complicated role of ROS-inducing agents in cancer therapy, more efforts are needed to verify the potential translational significance of our findings and search for specific inhibitors with less toxicity, e.g., those specifically target the BCAT1-engaged pathway other than non-selective ROS-inducing agents.…”
Section: Discussionmentioning
confidence: 99%
“…ROS are involved in countless metabolic processes that are essential for life, including adenosine triphosphate production, response to pathogens, cellular homeostasis and cell signaling (48)(49)(50). ROS have also been postulated by many to be causally involved in chemo brain (38,51). Anthracyclines like doxorubicin have been shown to result in the production of extremely high levels of ROS (37,38,52).…”
Section: Mitochondrial Biophoton Emissionmentioning
confidence: 99%